KINERJA PERBANKAN PADA KEPEMILIKAN: DOMESTIK, ASING, PEMERINTAH, DAN SWASTA - Andre Novado; Deny Dwi Hartomo (Magister Manajemen Fakultas Ekonomi dan Bisnis UNS, 2014)
This study aims to find empirical evidence on the effect of ownership on the performance of banks in Indonesia. This study uses secondary data with the observation period from 2005 to 2011. The population used in this study include domestic banks, foreign banks, state owned banks, and private banks, which have been listed on the Indonesian Stock Exchange. With purposive sampling method, 21 samples obtained.Proxies of the dependent variable, performance, are Return on Assets and Non-Performing Loans. While the independent variable, ownership, are proxied by Domestic-Foreign (DF) and State-owned Private (SP). In addition there are control variables like diversification (DIV), unutilized funds (GAP), firm size (SIZE), and firm age (AGE).The results of the test show that there is no significant effect of ownership on bank performance, except for the variable SP to NPL. The SP variable shows a negative significant effect on NPL. These results suggest that private banks have a better control on their credit risk. These indicates that using the DF and SP variables as proxies of ownership, to measure performance, which is proxied by ROA and NPL, are only relevant for the variable SP to NPL.